2021
DOI: 10.1007/s00402-021-04114-5
|View full text |Cite
|
Sign up to set email alerts
|

Robotics improves alignment accuracy and reduces early revision rates for UKA in the hands of low-volume UKA surgeons

Abstract: Purpose It is known that in uni-compartmental knee arthroplasty (UKA) low-volume surgeons have a higher complication and revision rate than high-volume surgeons. Further, robotic-assisted UKA leads to lower early revision rate as well as fewer limb and joint line outliers compared to conventional UKA. The purpose of this study was to retrospectively analyze the outliers’ and revision rate of low-volume UKA surgeons with different robotic systems at short-term follow-up. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…14 Considering Oxford UKA advantages in rebuilding knee kinematics and decreasing bearing wear, the introduction of this technique will benefit many patients. 15,16 In fact, this technical note is a refinement and complement of the currently popular Oxford UKA tutorial and fully highlights our experience. First, we summarized the five methods to sagittal tibial osteotomy, using two or more to check each other to increase the accuracy of osteotomy.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…14 Considering Oxford UKA advantages in rebuilding knee kinematics and decreasing bearing wear, the introduction of this technique will benefit many patients. 15,16 In fact, this technical note is a refinement and complement of the currently popular Oxford UKA tutorial and fully highlights our experience. First, we summarized the five methods to sagittal tibial osteotomy, using two or more to check each other to increase the accuracy of osteotomy.…”
Section: Discussionmentioning
confidence: 78%
“…UKA, a minimally invasive treatment therapy, has become prevalent with the development of technology for local knee arthritis 14 . Considering Oxford UKA advantages in rebuilding knee kinematics and decreasing bearing wear, the introduction of this technique will benefit many patients 15,16 . In fact, this technical note is a refinement and complement of the currently popular Oxford UKA tutorial and fully highlights our experience.…”
Section: Discussionmentioning
confidence: 88%
“…2123 For UKA specifically, low-volume surgeons have higher revision rates, and robotics reduce revision and improve alignment in the hands of these surgeons. 24,25 Prior literature also suggests that computer navigation improves trochlear rotation in PFA, and smaller studies of robotic-arm–assisted BKA have shown good results. 18,23 In this study, we did not find that improved revision rates after CA partial knee arthroplasty persisted at the 2-year time point.…”
Section: Discussionmentioning
confidence: 99%
“…coronal and sagittal planes. Assistive technologies, such as robotic-assisted systems, h been developed to improve the accuracy of bone resections and implant positioning UKA [8][9][10] with promising results [6,[11][12][13][14]. Due to the high cost of these devices, h ever, less than 1% of the surgeons in the world have access to a robotic-assisted system UKA.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The extramedullary guides for the tibial resection have been improved over time, but several studies reported a persistent high percentage of outliers [ 5 , 6 , 7 ] with a risk of error in coronal and sagittal planes. Assistive technologies, such as robotic-assisted systems, have been developed to improve the accuracy of bone resections and implant positioning in UKA [ 8 , 9 , 10 ] with promising results [ 6 , 11 , 12 , 13 , 14 ]. Due to the high cost of these devices, however, less than 1% of the surgeons in the world have access to a robotic-assisted system for UKA.…”
Section: Introductionmentioning
confidence: 99%